Aboveground Herbivory Influences Belowground Defense Responses in Maize - Pingault, Lise; Basu, Saumik; Zogli, Prince; Williams, W. Paul; Palmer, Nathan; Sarath, Gautam; Louis, Joe (Frontiers in Ecology and Evolution, 2021)
The European corn borer (ECB; Ostrinia nubilalis) is an economically damaging insect pest of maize (Zea mays L.), an important cereal crop widely grown globally. Among inbred lines, the maize genotype Mp708 has shown resistance to diverse herbivorous insects, although several aspects of the defense mechanisms of Mp708 plants are yet to be explored. Here, the changes in root physiology arising from short-term feeding by ECB on the shoot tissues of Mp708 plants was evaluated directly using transcriptomics, and indirectly by observing growth of western corn rootworm (WCR; Diabrotica virgifera virgifera) larvae. Mp708 defense responses negatively impacted both ECB and WCR larval weights, providing evidence for changes in root physiology in response to ECB feeding on shoot tissues. There was a significant downregulation of the root transcriptomes following short-term ECB feeding, including genes needed for direct defense (e.g., proteinase inhibitors and chitinases). Our transcriptomic analysis also revealed specific regulation of the genes involved in hormonal and metabolite pathways in the roots of Mp708 plants subjected to ECB herbivory. These data provide support for the long distance signaling-mediated defense in Mp708 plants and suggest that altered metabolite profiles of roots in response to ECB feeding of shoots likely negatively impacted WCR growth.